Lawyer's liability in negligence to third parties / Norlida A. Rani - A. Rani, Norlida (1986)
The aim of this project paper is to fullfil one of the requirements of the Diploma in Law course at the MARA Institute of Technology, Shah Alam. It is considered as one subject by itself. The discussion of this paper is centred primarily on decided cases mostly English cases are referred to because there are not many Malaysian case on point. But due to lack of time in which to complete this paper this discussion of lawyer's liability to the third parties is not exhaustive, there are still many areas that need to be discussed.